Thơ mới Việt Nam trong bối cảnh hiện đại hóa thơ ca Đông Á nửa đầu thế kỷ XX - Kiều, Thanh Uyên (Trường Đại học Cần Thơ, 2023)
The Vietnamese New Poetry Movement is one of the outstanding achievements of the modernization of Vietnamese literature in the first half of the twentieth century. Moreover, the New Poetry movement has contributed to bringing Vietnamese literature out of regional influence and catching up with the world literature trend. This paper mainly points out and analyzes the characteristics and nature of the Vietnamese New Poetry movement from the context of modernizing East Asian poetry.